2023
DOI: 10.3390/ani13182861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan on Ruminal Fermentation and Microbial Communities, Methane Emissions, and Productive Performance of Dairy Cattle

Jagoba Rey,
Xabier Díaz de Otálora,
Raquel Atxaerandio
et al.

Abstract: This study aimed to expand the knowledge about the activity and mode of action of CHI on methanogenesis and rumen microbial populations in vivo. A total of 16 lactating dairy cows were distributed in two groups, one of them receiving 135 mg CHI/kg body weight daily. The effect on productive performance, milk composition, fermentation efficiency, methane emissions, microbial protein synthesis, and ruminal microbial communities was determined. Supplementation with CHI did not affect rumen microbial diversity but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…In this study, it was observed that the number of rumen protozoa in the 0.08% COS group was lower than that in the CON group during the sampling period. In previous studies on chitosan, similar results were obtained, namely that chitosan reduced the number of protozoa [ 33 , 41 ]. Previous studies have shown that changes in the number of rumen protozoa are related to eating and drinking behaviour [ 42 , 43 ], protein supply in the diet [ 44 ], and abundance of rumen bacterial communities [ 45 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, it was observed that the number of rumen protozoa in the 0.08% COS group was lower than that in the CON group during the sampling period. In previous studies on chitosan, similar results were obtained, namely that chitosan reduced the number of protozoa [ 33 , 41 ]. Previous studies have shown that changes in the number of rumen protozoa are related to eating and drinking behaviour [ 42 , 43 ], protein supply in the diet [ 44 ], and abundance of rumen bacterial communities [ 45 ].…”
Section: Discussionsupporting
confidence: 76%
“…The changes in NH 3 -N concentration are consistent with the results of the Goiri [ 50 ] and Zanferari [ 67 ] studies, but many studies on changes in MCP have produced inconsistent results. For example, the studies of Seankamthorn [ 76 ] and Rey [ 41 ] mentioned that the addition of chitosan has no significant effect on MCP. Whereas Gandra’s research also found that chitosan as an additive led to a decrease in MCP levels [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Volatile fatty acids content was determined by the Agilent 7890B meteorological chromatograph. After the rumen fluid sample was pretreated, it was injected into a gas chromatograph to obtain the chromatogram of VFAs sample, then we calculated the content of VFAs using the peak area external standard method [ 23 ]. Ammonia nitrogen content was determined by the phenol-sodium hypochlorite colorimetric method.…”
Section: Methodsmentioning
confidence: 99%